2019
DOI: 10.1029/2018jb016382
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Gradiometry With GRACE Space Missions: New Opportunities for the Geosciences

Abstract: A new paradigm views the recently launched Gravity Recovery and Climate Experiment (GRACE) follow‐on mission as a gradiometer system, outside the mission's design concept, promising potentially major implications in geosciences. We develop an innovative and straightforward concept, the “GRACE gradiometer mode,” to process future GRACE follow‐on measurements to derive three‐dimensional gravitational gradients. Using positions, accelerations, and attitude measurements from the identical predecessor mission GRACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…At present, a large amount of data has been accumulated from the space systems GRACE (2002-2017) and GRACE-FO (from 2018 to the present) [6]. On the basis of this information, the space-time variations of the Earth's gravity field with a period of 30 days are studied [7,8]. The GRACE CS implements the Satellite-to-Satellite Tracking (SST) method [8].…”
Section: Application Of the Grace Technology For Solving Geomonitorin...mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, a large amount of data has been accumulated from the space systems GRACE (2002-2017) and GRACE-FO (from 2018 to the present) [6]. On the basis of this information, the space-time variations of the Earth's gravity field with a period of 30 days are studied [7,8]. The GRACE CS implements the Satellite-to-Satellite Tracking (SST) method [8].…”
Section: Application Of the Grace Technology For Solving Geomonitorin...mentioning
confidence: 99%
“…On the basis of this information, the space-time variations of the Earth's gravity field with a period of 30 days are studied [7,8]. The GRACE CS implements the Satellite-to-Satellite Tracking (SST) method [8]. High-precision positioning of Grace 1 and Grace 2 is provided by linking to the GPS navigation system.…”
Section: Application Of the Grace Technology For Solving Geomonitorin...mentioning
confidence: 99%
“…Before and after the 1964 Alaska earthquake, the 1965-1967 Songdai earthquake swarm in Japan, the 1974 Izu earthquake in Japan, the 1976 Gazley earthquake swarm in the Soviet Union, and the 2013 M s 7.0 Lushan earthquake and gravity drop after the mainshock (Barnes, 1966;Wang LH et al, 2023Zhu YQ et al, 2023, the time-varying information on gravity before earthquakes was observed with time series of absolute and relative gravity data. The gravity data obtained by the Gravity Recovery And Climate Experiment (GRACE), which is representative of gravity satellite technology, contains information on the crustal density distribution and can be used to study the interaction mechanism between and within plates before earthquakes (Wahr et al, 1998;Peidou and Pagiatakis, 2019;Zotin et al, 2019;Gido et al, 2020;Velicogna et al, 2020;Liu C and Sun WK, 2023). Sun W and Okubo (2004) studied whether the GRACE satellites could detect coseismic gravity changes based on dislocation theory and concluded that GRACE is capable of detecting coseismic deformation signals from earthquakes with a magnitude greater than 7.5.…”
Section: Introductionmentioning
confidence: 99%